Organic photovoltaic cell taking sulfur-doped MoO3 film as anode interface layer and preparation method thereof - QIN ZHONGLI; YU XUELI; LI DUANYONG; ZHANG YU; QIN PINGLI (2013)
The invention relates to an organic photovoltaic cell taking a sulfur-doped MoO3 film as an anode interface layer and a preparation method thereof. The organic photovoltaic cell taking the sulfur-doped MoO3 film as the anode interface layer comprises an oxide transparent conducting substrate, an anode interface layer, an organic photosensitive active layer and metal electrodes, wherein the anode interface layer is a sulfur-doped MoO3 film deposited from an MoS2 target on the oxide transparent conducting substrate by using a magnetron sputtering system through changing the argon-to-oxygen ratio in the working atmosphere while depositing the film. The organic photovoltaic cell has the benefits that the causticity to ITO (Indium Tin Oxides) is avoided, and the heat stability is excellent. Compared with the traditional prepared MoO3 film, the sulfur-doped MoO3 film prepared through adopting the method reduces defects of the MoO3 film, especially the defect on the surface, facilitates improving an interface betwee